PAKAIAN DEPATI NINIK MAMAK DAN DAYANG-DAYANG KECAMATAN KUMUN DEBAI DALAM FOTOGRAFI KONSEPTUAL - Vina Damayanti; Aziz Fauzi Rahmat (Kirana Publisher, 2026)
This photographic creation aims to represent and reaffirm the cultural values and customary identity embedded in the traditional attire of Depati, Ninik Mamak, and Dayang-dayang in Kumun Debai District, Sungai Penuh City, through a conceptual photography approach. The traditional attire functions as a symbol of status, authority, and social roles within the customary system of the community, particularly in the implementation of the Kenduri Sko ceremony. The creative method includes field observation, interviews with traditional leaders, literature study, visual concept development, photographic production, and post-production processes. The visual concept emphasizes details of the traditional garments, subject expressions, the use of customary properties, as well as the application of composition, lighting, and camera angles to strengthen the symbolic meaning of the attire. This work functions not only as visual documentation but also as a medium of artistic interpretation, expected to raise awareness of the importance of cultural preservation and to reinforce the cultural identity of the Kumun Debai community through the medium of photography.